2014
DOI: 10.5045/br.2014.49.2.107
|View full text |Cite
|
Sign up to set email alerts
|

R-CHOP chemoimmunotherapy followed by autologous transplantation for the treatment of diffuse large B-cell lymphoma

Abstract: BackgroundWe investigated factors that influence outcomes in diffuse large B-cell lymphoma (DLBCL) patients treated with rituximab combined with the CHOP regimen (R-CHOP) followed by upfront autologous stem cell transplantation (Auto-SCT).MethodsWe retrospectively evaluated survival differences between subgroups based on the age-adjusted International Prognostic Index (aaIPI) and revised-IPI (R-IPI) at diagnosis, disease status, and positron emission tomographic/computerized tomographic (PET/CT) status at tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…DLBCL might be the most common histological subtype of NHL, corresponding to 30-40% of cases in adults [16,17,19]. MCL, like DLBCL, is an aggressive subtype of lymphoma, which, compared with distinct lymphoma, has diversified outcomes after a series of therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DLBCL might be the most common histological subtype of NHL, corresponding to 30-40% of cases in adults [16,17,19]. MCL, like DLBCL, is an aggressive subtype of lymphoma, which, compared with distinct lymphoma, has diversified outcomes after a series of therapies.…”
Section: Discussionmentioning
confidence: 99%
“…HR, hazard ratio; OS, overall survival; PFS, progression-free survival; SCT, stem cell transplantation. Smeltzer et al [14] Mocikova et al [15] Devillier et al [16] Lee et al [17] Armand et al [18] Qiao et al [19] Derenzini et al [20] Hoppe et al [21] Qiao et al [22] Cremerius et al [23] Schot et al [24] Schot et al [26] Crocchiolo et al [28] Samaras et al [29] Note: Weights are from random effects analysis high-quality studies. Stars were then added up and used to compare the quality of the study quantitatively [9].…”
Section: Selection Of Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…A randomized trial including patients treated with chemoimmunotherapy revealed that upfront ASCT improved progression-free survival (PFS) in aggressive NHL with a high-intermediate or high-risk IPI [11]. Recent studies reported that upfront ASCT improved OS in patients aged <50 years with good performance status at diagnosis in high-risk DLBCL and the unfavorable outcomes attributed to partial response (PR) after R-CHOP [12,13]. ASCT in first remission may provide survival benefits, as it removes minimally residual disease, and it may also have survival benefits for highly selected patients who have achieved CR [14].…”
Section: Introductionmentioning
confidence: 98%
“…Rituximab (chimeric anti-CD20 monoclonal antibody) is an important therapeutic tool, since NHLs are characterized by CD20 expression, and is used in combination with one or more antiblastic drugs [1][2][3][4][5][6] and for maintenance therapy after first-line chemo-immunotherapy [7].…”
Section: Introductionmentioning
confidence: 99%